2021
DOI: 10.1111/apm.13178
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic and reverse zoonotic transmission of viruses between humans and pigs

Abstract: Humans and pigs share a close contact relationship, similar biological traits, and one of the highest estimated number of viruses compared to other mammalian species. The contribution and directionality of viral exchange between humans and pigs remain unclear for some of these viruses, but their transmission routes are important to characterize in order to prevent outbreaks of disease in both host species. This review collects and assesses the evidence to determine the likely transmission route of 27 viruses b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…This study confirmed SwIAV viral circulation in wild boars and represents an upgrade on the research into the Italian situation. Considering the Sus scrofa species’ role in the development of reassortant strains, which are agents of spillover infections, and livestock’s potential role as an epidemiological bridge between wildlife and humans [ 1 , 2 ], the dynamic control of the viral hypervariability through systematic surveillance against SwIAVs in the wild boar population is certainly needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirmed SwIAV viral circulation in wild boars and represents an upgrade on the research into the Italian situation. Considering the Sus scrofa species’ role in the development of reassortant strains, which are agents of spillover infections, and livestock’s potential role as an epidemiological bridge between wildlife and humans [ 1 , 2 ], the dynamic control of the viral hypervariability through systematic surveillance against SwIAVs in the wild boar population is certainly needed.…”
Section: Discussionmentioning
confidence: 99%
“…Wildlife viruses can easily spill over into human and domestic animal populations, representing an underinvestigated burden for both public and veterinary health [ 1 , 2 ]. Influenza viruses (IVs), belonging to the genus Influenzavirus A (IAV) within the Orthomyxoviridae family, are the most widespread agents of respiratory infections in humans and swine ( Suidae ) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are an estimated 40, 000 viral species circulating in mammals, a quarter of which have zoonotic potential (188); in particular, many of the recent epidemics of emerging respiratory viruses are believed to have originated in wildlife (189, 190). The reverse can also occur where reverse zoonosis or anthroponosis contributes to the diversity of viral species in animals that have high interactions with humans (191). The dynamic relationship between humans and animal species and the associated diseases not only put the persistence of wildlife populations at risk (e.g., bighorn sheep pneumonia (192)) but also pose a risk for transmission to domesticated livestock (193) and humans (178) Thus, these events threaten both public health and food security.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, the infection of mink farms in multiple countries was a strong reminder of the importance of One‐Health surveillance. The constitution of a non‐human reservoir from where the virus could spill back into humans is a major concern, as exemplified by multiple viruses, including influenza, with documented cases of human‐to‐swine‐to‐human transmission (Glud et al , 2021). Importantly, the intensive circulation of an emerging virus in a new host leads to the accumulation of amino acid changes, some reflecting adaptation to this novel environment, which could result in the evolution of variants with unpredictable properties with regard to human infection.…”
Section: Figure Amino Acid Changes In the Receptor–binding Domain (Rb...mentioning
confidence: 99%
“…Importantly, the intensive circulation of an emerging virus in a new host leads to the accumulation of amino acid changes, some reflecting adaptation to this novel environment, which could result in the evolution of variants with unpredictable properties with regard to human infection. As a case in point, SARS-CoV-2 spillback from minks to humans in Denmark was associated with lower capability of preexisting human antibodies to neutralize the variant (Larsen et al, 2021).…”
mentioning
confidence: 93%